Choosing the optimal stent in malignant extrahepatic biliary obstruction: What is the most pertinent outcome?. Issue 5 (22nd May 2022) - Perez‐Cuadrado‐Robles, Enrique; Becq, Aymeric; Rahmi, Gabriel
Abstract : This Editorial refers to the article by Y. Yamashita et al., p 938–951 of the issue DEN 34:5.